Kota Cerdas Dan Mobilitas Cerdas: Sebuah Tinjauan Literatur - Gary Ekatama Bangun; I Made Suwandi (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2022)
Cities have a variety of issues that arise. Today's advancements in information and communication technology provide many benefits to human life, including urban management. This article discusses Smart City or Smart City, as well as one of its aspects, Smart Mobility or Smart Mobility. The research method used is a literature review or study of journal articles, books, and previous studies on this research topic. According to the study's findings, Smart City is a concept that combines information and communication technology with urban infrastructure, of course, this integration is also carried out on transportation infrastructure to facilitate public access to public transportation infrastructure and also traffic conditions easily, this also known as smart mobility make it easier to manage urban areas, and then to capture public opinion through digital applications, and manage information to make decisions and policy. Easy public access to transportation infrastructure is also expected to increase public interest in switching to public transportation and changing their behavior patterns in traffic.